Mutational Replacement of Leu-293 in the Class C Enterobacter cloacae P99 β-Lactamase Confers Increased MIC of Cefepime - Vakulenko, Sergei B. (American Society for Microbiology, 2002)
The class C β-lactamase from Enterobacter cloacae P99 confers resistance to a wide range of broad-spectrum β-lactams but not to the newer cephalosporin cefepime. Using PCR mutagenesis of the E. cloacae P99 ampC gene, we obtained a Leu-293-Pro mutant of the P99 β-lactamase conferring a higher MIC of cefepime (MIC, 8 μg/ml, compared with 0.5 μg/ml conferred by the wild-type enzyme). In addition, the mutant enzyme produced higher resistance to ceftazidime but not to the other β-lactams tested. Mutants with 15 other replacements of Leu-293 were prepared by site-directed random mutagenesis. None of these mutant enzymes conferred MICs of cefepime higher than that conferred by Leu-293-Pro. We determined the kinetic parameters of the purified E. cloacae P99 β-lactamase and the Leu-293-Pro mutant enzyme. The catalytic efficiencies (k(cat)/K(m)) of the Leu-293-Pro mutant β-lactamase for cefepime and ceftazidime were increased relative to the respective catalytic efficiencies of the wild-type P99 β-lactamase. These differences likely contribute to the higher MICs of cefepime and ceftazidime conferred by this mutant β-lactamase.